Extract of Caesalpinia sappan L. as Antibacterial Feed Additive on Intestinal Microflora of Laying Quail - Widigdyo, Anang; Widodo, Eko; Djunaidi, Irfan Hadji (The Journal of Experimental Life Science, 2017)
Caesalpinia sappan L. is a phytobiotic plant that serves as an antibacterial. Active compound such as flavonoids in the C. sappan L. extract acts as an antibacterial. TheÂ  protein food sources in Indonesia including poultry such as quail. Several studies demonstrated that quail are very susceptible to bacterial infections including Escherichia coli and Salmonella. Thus C. sappan has been used as food additive for quail in laying eggs. This research objective was to study the effects of C. sappan L. extract against intestinal miclofora of quail in laying eggs. This study used 168 quails with 4 treatments and 5 replications, each treatment used 7 quails. This study used 4 Wood Extract C. sappan L. treatment with different concentrations including 0%, 0.2%, 0.4%, 0.6%. The results showed that administration of Extract Wood C. sappan L. was not significantly different (P> 0.05) to the total number of bacteria E. coli with the average P0 (6.0903 Log CFU), P1 (6.0903 log CFU), P2 (6.0887 Log CFU), and P3 (6.0868 Log CFU). Meanwhile, it was significantly different (P <0.05) to the total number of Salmonella bacteria in the gut laying with the average number of bacteria P0 (5.4059 Log CFU), P1 (5.4048 Log CFU), P2 (5.4045 Log CFU), and P3 (5.4039 Log CFU). It is concluded that flavonoids compounds in C. sappan L. extract could decrease the number of Salmonella, but not E. coli, in the intestine of quail.Keywords: Caesalpinia sappan L., Eschericia coli, Flavonoid, Salmonella.